Falsafah Kepemimpinan Rasulullah - Nanang Tahqiq (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2007)
Prophet Muhammad (PBUH) is known as the most successful prophet in fulfilling his mission. He was appointed as a messenger at the age of 40, a mature age. This indicates that such a title and status were not achieved without struggle, but after he matured and was tempered by many experiences. This article attempts to address questions about the success of Prophet Muhammad's leadership, asking whether all of the Prophet's successes were due to God's intervention. If God is involved, what makes Muhammad special? Doesn't that mean Muhammad did not undergo a process like an ordinary human? If he is “not an ordinary human,” then how can we emulate and consider him as a role model in leadership?